Uptake of Efficient Marketing Strategies among Footwear and Textile Entrepreneurs in Alexandra Township - Worku, Yohannes; Muchie, Mammo (Journal of Economics and Behavioral Studies, 2018)
One of the priority needs of Small, Micro and Medium-Sized Enterprises (SMMEs) that operate in Alexandra Township is to adopt effective marketing strategies that are recommended by Mooradian, Matzler and Ring (2012) and Kotler and Keller (2012), in which emphasis is placed on setting the right selling price of products, offering the right product, utilising the right promotion strategies for products, and rendering services to customers at the right place. Information needed for the survey was gathered from 108 operators of SMMEs in Alexandra Township. Ordered logit and Bayesian methods were used for estimating predictors of effective marketing. The study found that 63 of the 108 respondents who were selected for the study (58%) possessed adequate marketing skills and capabilities, whereas the remaining 45 respondents (42.23%) were incapable of marketing their goods and services effectively. Results obtained from logit and Bayesian analysis showed that 3 factors affected the ability to market goods and services effectively (access to credit facility for ordering stock, access to loan from money-lending institutions, and ability to network with wholesale suppliers and retailers).